Site‐directed mutagenesis of the P225, N230 and H272 residues of succinate dehydrogenase subunit B from Botrytis cinerea highlights different roles in enzyme activity and inhibitor binding. (10th October 2013) - Lalève, Anaïs; Gamet, Stéphanie; Walker, Anne‐Sophie; Debieu, Danièle; Toquin, Valérie; Fillinger, Sabine
Summary Carboxamide fungicides target succinate dehydrogenase (SDH). Recent field monitoring studies have identified Botrytis cinerea isolates resistant to one or several SDH inhibitors (SDHIs) with amino acid substitutions in the SDH B subunit. We confirmed, by site‐directed mutagenesis of the sdhB gene, that each of the mutations identified in field strains conferred resistance to boscalid in B. cinerea, and in some cases cross‐resistance to other SDHIs (fluopyram, carboxin). Enzyme inhibition studies showed that the studied modifications (SdhB_P225T/L/F, N230I, H272Y/R/L) affected the inhibition of SDH activity by SDHIs, directly contributing to resistance. Our results confirm the importance of H272, P225 and N230 for carboxamide binding. Modifications of P225 and N230 conferred resistance to the four carboxamides tested (boscalid, fluopyram, carboxin, bixafen). Modifications of H272 had differential effects on the susceptibility of SDH to SDHIs. SdhBH272L, affected susceptibility to all SDHIs, SdhBH272R conferred resistance to all SDHIs tested except fluopyram, and SdhBH272Y conferred fluopyram hypersensitivity. Affinity‐binding studies with radiolabelled fluopyram revealed strong correlations among the affinity of SDHIs for SDH, SDH inhibition and in vivo growth inhibition in the wild type. The sdhBH272Y mutation did not affect SDH and respiration activities, whereas all the other mutations affected respiration by decreasing SDH activity.